Interpretation : making a difference on purpose - Ham, Sam H. (Golden, Colorado : Fulcrum Publishing, 2013)
"This book provides a treasure trove of how-to methods and ways to approach developing personal and non-personal heritage interpretation products."--Publisher.
Interpretation and communication -- TORE -- The endgame of interpretation -- Can all interpretation make some kind of difference? -- Making a difference on purpose -- Two sides of theme and sentences in the head -- Not all themes are equal -- The zone of tolerance -- Sequential theme development -- Nonsequential theme development.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Natural areas -- Interpretive programs; Environmental education; National parks and reserves -- Interpretive programs; Environmental education; National parks and reserves -- Interpretive programs; Natural areas -- Interpretive programs; Pedagogik; Kulturarv